Antibiotic Susceptibility Patterns of Bacterial Isolates from Pus Samples in a Tertiary Care Hospital of Punjab, India - Rugira Trojan; Lovely Razdan; Nasib Singh (International Journal of Microbiology)
We determined the prevalence and antibiotic susceptibilities patterns of bacterial isolates from pus samples collected from patients in a tertiary care hospital of Punjab, India. E. coli was the most prevalent pathogen (51.2%) followed by Staphylococcus aureus (21%), Klebsiella pneumoniae (11.6%), Pseudomonas aeruginosa (5.8%), Citrobacter spp. (3.5%), Acinetobacter baumannii (2.3%), Proteus mirabilis (2.3%), and Streptococcus spp. (2.3%). E. coli, K. pneumoniae, A. baumannii, and Citrobacter isolates were resistant to multiple antibiotics including higher generation cephalosporins. S. aureus and Streptococcus isolates were sensitive to cloxacillin and vancomycin. However, P. aeruginosa, P. mirabilis, and Streptococcus isolates were found to be less resistant to the spectrum of antibiotics tested. Overall, our findings indicate the prevalence of resistance to different classes of antibiotics in bacterial isolates from pus infections and hence highlight the need for effective surveillance, regulator reporting, and antibiogram-guided antibiotic prescription.